THE IMPACT OF INNOVATION STRATEGY ON ORGANIZATIONAL LEARNING AND INNOVATION PERFORMANCE: DO FIRM SIZE AND OWNERSHIP TYPE MAKE A DIFFERENCE? - Beyene, Kinfe Tsegay; Shi, Chun Sheng; Wu, Wei Wei (The South African Journal of Industrial Engineering, 2016)
Though innovation strategy and organizational learning have been credited to impact on product innovation performance, they have been rarely considered in a single model simultaneously. Thus, the main aim of the paper is to investigate the extent of impact of innovation strategy on organizational learning and product innovation performance. A structural equation modelling analysis was performed on the survey data collected from Ethiopian textile and leather product manufacturing firms. The result reveals that innovation strategy is positively related to product innovation performance. Further, firm size and ownership type moderate the effect of innovation strategy on product innovation performance.